PROSPER partnership delivery system: Effects on adolescent conduct problem behavior outcomes through 6.5 years past baseline. (December 2015) - Spoth, Richard L.; Trudeau, Linda S.; Redmond, Cleve; Shin, Chungyeol; Greenberg, Mark T.; Feinberg, Mark E.; Hyun, Gee-Hong
Abstract: We report long-term effects of the PROSPER delivery system for universal evidence-based preventive interventions on adolescent conduct problem behaviors (CPBs). A cluster randomized trial included 28 school districts assigned to PROSPER or a control condition. Community-based teams in PROSPER condition school districts selected evidence-based interventions—a family-focused intervention in sixth grade and a school-based intervention the next year; follow-up assessments were conducted through 12th grade. CPBs were measured with 12 self-report items derived from the National Youth Survey. Intervention-control differences were tested via a multi-level Zero-Inflated Poisson (ZIP) model. Differences were significant from 9th through 12th grades; Relative Reduction Rates were between 10.1% and 14.5%. The intervention group was delayed in reaching a 10th grade reference level of CPBs by 10.7 months. Moderation analyses indicated stronger effects for early substance initiators. Findings suggest that the PROSPER delivery system has the potential to reduce CPBs in general populations.